Explanatory and Confirmatory Qualifications of Christian Leaders Based on the Book of Titus 1 Among Synod Officials of the Pentecostal Church Indonesian Jesus Christ - Fransisco, Leo; Daliman, Muner; Purwoko, Paulus Sentot; Sugiyarto, Kristian Handoyo (Technium Social Sciences Journal, 2023)
This research was among synod officials of the Indonesian Isa Almasih Pentecostal Church, and has experienced growth both in quality and quantity. Along with the growth of the church, the church leader or pastor appoints his leadership qualifications to assist in stewardship tasks among synod officials of the Isa Almasih Pamtekosta Church in Indonesia. The purpose of this study is to find out how the qualifications of Christian leaders are carried out by synod officials of the Isa Almasih Pantekosta Church in Indonesia. This study used a quantitative method, where data were obtained through questionnaires, interviews and a standardized scale. Questionnaire validation at the initial stage tested all validated questionnaire scores filled in by the promoter to be tested on 30 initial samples.The conclusion of this research is basedanalysis resultsusing Classification and regression trees (CRT)shows that age background is the most dominant background category forming the Confirmation of Qualifications of Christian leaders based on the book of Titus chapter 1 among synod officials of the Pentecostal Church of Isa Almasih Indonesia(Y). From the suragates table it is known that age background is able to improve by 111,063 points from the condition of the Implementation of the Qualifications of Christian leaders based on the book of Titus article 1 among synod officials of the Pentecostal Church of Isa Almasih Indonesia (Y) . As well as from the importance table it is known that background employment status is affirmed by 100% of respondents with a score of 231.093 points.